SYNERGISTIC EFFECT LUNG CANCER THERAPY: CO-DELIVERY OF QUERCETIN AND CISPLATIN VIA EUDRAGIT L-100 NANOPARTICLES IN VITRO - AL-MAMOORI, FIRAS F.; WAHAB, HABIBAH A.; AHMAD, WAQAS (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to investigate the potential of Eudragit L-100 nanoparticles for the co-delivery of quercetin and cisplatin to lung cancer cells, seeking to exploit the synergistic effects of the two drugs while overcoming their individual limitations. Methods: We investigate the synergistic effect of co-delivering quercetin and cisplatin using Eudragit L-100 nanoparticles for lung cancer therapy. The nanoparticles were synthesized using the nanoprecipitation method, where Eudragit L-100 was dissolved in an organic solvent, followed by the incorporation of quercetin and cisplatin. The resultant nanoparticles were characterized for size, zeta potential, drug loading efficiency, and morphology using techniques such as Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM). Results: The co-loaded Quercetin-Cisplatin Nanoparticles (Qu-Cis)-NPs formulation had a mean particle size of 475±4.77 nm. Polydispersion index of 0.266±0.093 and zeta potential was-24.03±0.89 mV. The in vitro cytotoxicity was assessed using normal cell and lung cancer cell lines in vitro studies showed that the developed nanoparticles significantly increased cancer cell mortality compared to individual drug treatments. The combination (Qu-Cis)-NPs showed more cytotoxicity on the Non-Small Lung Cancer Cell Line (NCI-H460) cancer cell line after 48 h of incubation compared to Qu loaded-NPs and Cis loaded-NPs, particularly at a concentration of 1 mg/ml. The combination showed no cytotoxicity effect on normal Human Lung fibroblast cell Lines (CCD-19 lu) cells at all concentrations after 24 h, but showed cytotoxicity effects at concentrations (0.125, 0.25, 0.5, and 1.0) mg/ml after 48 h. Conclusion: The Eudragit L-100 nanoparticle system for co-delivering quercetin and cisplatin showed a promising synergistic effect in lung cancer treatment. It effectively addresses the solubility and toxicity issues of both drugs, offering a potentially more effective treatment option that merits further clinical investigation.